2012
DOI: 10.1159/000336823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Endothelin A Receptor and Renin-Angiotensin System Blockade on the Course of End-Organ Damage in 5/6 Nephrectomized Ren-2 Hypertensive Rats

Abstract: Our previous studies in rats with ablation nephrectomy have shown similar cardiorenal protective effects of renin-angiotensin system (RAS)-dependent treatment (combination of angiotensin-converting enzyme inhibitor and angiotensin II receptor blocker) and RAS-independent treatment (combination of α- and β-adrenoreceptor antagonist and diuretics). Moreover, selective blockade of endothelin (ET) receptor type A (ETA) improved survival rate and attenuated hypertension and organ damage in Ren-2 transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 63 publications
6
45
0
Order By: Relevance
“…These findings are in accordance with previous studies showing that heterozygous TGR without any intervention (e.g. high salt or 5/6 NX) exhibit high resistance to the development of hypertension‐induced renal damage . In contrast, untreated 5/6 NX TGR exhibited significantly lower creatinine clearance (especially 8 weeks after 5/6 NX, just before the first rats began to die) compared with sham‐operated TGR.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in accordance with previous studies showing that heterozygous TGR without any intervention (e.g. high salt or 5/6 NX) exhibit high resistance to the development of hypertension‐induced renal damage . In contrast, untreated 5/6 NX TGR exhibited significantly lower creatinine clearance (especially 8 weeks after 5/6 NX, just before the first rats began to die) compared with sham‐operated TGR.…”
Section: Resultssupporting
confidence: 92%
“…However, it is clear that different renal diseases exhibit common pathomorphological signs, such as tubulointerstitial fibrosis and tubular atrophy, followed by glomerulosclerosis . The studies using the 5/6 NX model have demonstrated that hypertension and inappropriately activated renin–angiotensin system (RAS) are two critical determinants of the progression rate of CKD to ESRD . In addition, both experimental and clinical studies have shown that RAS blocking agents, such as angiotensin‐converting enzyme inhibitors (ACEI) and angiotensin (Ang) II receptor blockers (ARBs), are highly effective inhibitors of the progression of CKD (renoprotective action) .…”
Section: Introductionmentioning
confidence: 99%
“…Tubulointerstitial injury was defined as tubular dilatation, atrophy, cast formation and sloughing of tubular epithelial cells or thickening of tubular basement membrane and scaring as follows grade 0, no injury; grade 1, tubulointerstitial injury in less than 25%; grade 2, (25–50%); grade 3, (>50%). This approach is now routinely used in our laboratory and allows comparison of the present results with those of our previous and also future studies evaluating the pathophysiology of hypertension-associated end-organ damage [7,9,13,20,25,27]. …”
Section: Methodsmentioning
confidence: 89%
“…Atrasentan improved the survival rate, reduced blood pressure, attenuated the development of cardiac hypertrophy, and transiently reduced proteinuria. Combination therapy did not provide additive protection [25]. …”
Section: Discussionmentioning
confidence: 99%